2016
DOI: 10.1111/jopr.12530
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Management: An Overview of the Literature

Abstract: Studies showed an enhancement in the quality of life in many patients who have been treated with oral appliances, and patients in general prefer oral appliances over CPAP therapy or any other treatments for OSA because of its convenience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 74 publications
(103 reference statements)
0
14
0
Order By: Relevance
“…Behaviour modification is to train the patient to alter the sleep position to a lateral position instead of supine position by using a pillow, advising patients to abstain from alcohol and to control on a diet. Encourage them to do regular exercise and monitor the body weight and motivate the patients to reduce if they are overweight [16], [17], [18], [19]. Some studies suggested the use of mild sedative 3hours before sleep which are helpful to promote sound sleep, other medication advised for OSA are antibiotics, topical intranasal application of corticosteroid, leukotriene receptor antagonist and anti-inflammatory therapy to a mild to moderate case and during maintenance therapy after surgery [18], [19].…”
Section: Discussionmentioning
confidence: 99%
“…Behaviour modification is to train the patient to alter the sleep position to a lateral position instead of supine position by using a pillow, advising patients to abstain from alcohol and to control on a diet. Encourage them to do regular exercise and monitor the body weight and motivate the patients to reduce if they are overweight [16], [17], [18], [19]. Some studies suggested the use of mild sedative 3hours before sleep which are helpful to promote sound sleep, other medication advised for OSA are antibiotics, topical intranasal application of corticosteroid, leukotriene receptor antagonist and anti-inflammatory therapy to a mild to moderate case and during maintenance therapy after surgery [18], [19].…”
Section: Discussionmentioning
confidence: 99%
“…Reversible treatments include use of a continuous positive airway pressure (CPAP) or mandibular advancement device (MAD), and behavioural treatments, such as weight loss and/or alteration of the sleep position. Irreversible treatments include orthodontic treatment and varies kinds of surgeries …”
Section: Introductionmentioning
confidence: 99%
“…Among the various investigations used to diagnose OSA, polysomnography (PSG) is considered as the most reliable method of detecting the frequency of apneic and hypopneic events during sleep. 11 Under standardized conditions, PSG determines sleep time, stages of sleep, respiratory effort and airflow, cardiac rhythm, pulse oximetry for blood oxygen saturation, and abdominal, thoracic and limb movements through multichannel recordings. 4 In addition, overnight pulse oximetry assessment has also been reported recently as a diagnostic aid equivalent to that of PSG, and with sensitivity as high as 98%.…”
mentioning
confidence: 99%